2012
DOI: 10.1631/jzus.b1200022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total dissolved gas supersaturated water on lethality and catalase activity of Chinese sucker (Myxocyprinus asiaticus Bleeker)

Abstract: Total dissolved gas (TDG) supersaturation caused by dam sluicing can result in gas bubble trauma (GBT) in fish and threaten their survival. In the present study, Chinese suckers (Myxocyprinus asiaticus Bleeker) were exposed to TDG supersaturated water at levels ranging from 120% to 145% for 48 h. The median lethal concentration (LC(50)) and the median lethal time (LT(50)) were determined to evaluate acute lethal effects on Chinese suckers. The results showed that the LC(50) values of 4, 6, 8, and 10 h were 142… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 13 publications
4
44
0
Order By: Relevance
“…However, when TDG supersaturation was 130% and higher, differences in tolerance to TDG-supersaturated water were not evident between the two species. Chen et al (2012) reported Chinese Sucker weights and lengths of 39.54 § 7.63 g (mean § SD) and 11.54 § 0.91 cm, respectively, which were larger than the Prenant's Schizothoracin used in this study. We suggest that the life stage and species affected the tolerance of the two fish species and caused differences between them at lower TDG supersaturation levels (125% and less); however, the survival time was not affected by the two factors when TDG supersaturation exceeded a tolerable threshold (130% and higher).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…However, when TDG supersaturation was 130% and higher, differences in tolerance to TDG-supersaturated water were not evident between the two species. Chen et al (2012) reported Chinese Sucker weights and lengths of 39.54 § 7.63 g (mean § SD) and 11.54 § 0.91 cm, respectively, which were larger than the Prenant's Schizothoracin used in this study. We suggest that the life stage and species affected the tolerance of the two fish species and caused differences between them at lower TDG supersaturation levels (125% and less); however, the survival time was not affected by the two factors when TDG supersaturation exceeded a tolerable threshold (130% and higher).…”
Section: Discussionmentioning
confidence: 52%
“…However, Chinese Suckers exhibited a stronger tolerance than did Prenant's Schizothoracin to 125% TDG supersaturation (Figure 3). Dead Chinese Suckers were not observed by Chen et al (2012) at supersaturation levels of 120% or less. However, when TDG supersaturation was 130% and higher, differences in tolerance to TDG-supersaturated water were not evident between the two species.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Prior studies reveal that the injury to fish is enhanced as the supersaturated TDG level and exposure time increases (Bentley et al, 1976;Huang et al, 2010;Chen et al, 2012). The endurance of fish with respect to supersaturated TDG is different depending on the growth period for the fish species (Liang et al, 2013).…”
Section: The Previous Studiesmentioning
confidence: 99%